Thermal energy system with chilled water storage / Ibrahim Mohamad and Maliki Abdul Ghani - Mohamad, Ibrahim; Abdul Ghani, Maliki (1996)
In most modem office building or complex in tropical Malaysian climate, Heating, Ventilating and Air-Conditioning (HVAC) system are the largest energy consumers and offer the owners significant potential for savings. A substantial part of this energy consumption comes from the building chilled water system and specifically the chillers. This is because they operate during cooling climate zones, thereby contributing to peak energy demands, resulting in high electricity bill. The electricity bill normally contain the charges incur due to the use of electricity during the off-peak and on-peak hours together with maximum demand charges of the month. Thus, the objective of this project is to identify how the unique technological features offered by Thermal Energy Storage (TES) can be manipulated as an effective means of energy saving i.e. reducing energy cost on the central chilled water air-conditioning system for Engineering Faculty Complex, National University of Malaysia (UKM), Bangi, Selangor. The report consists of 7 chapters. The 'Introduction' present an overview on energy consumed and potential conservation in a building services sector mainly on air-conditioning system.